Community health workers in rural India: analysing the opportunities and challenges Accredited Social Health Activists (ASHAs) face in realising their multiple roles - Saprii, Lipekho (Hum Resour Health, 2015)
BACKGROUND: Globally, there is increasing interest in community health worker’s (CHW) performance; however, there are gaps in the evidence with respect to CHWs’ role in community participation and empowerment. Accredited Social Health Activists (ASHAs), whose roles include social activism, are the key cadre in India’s CHW programme which is designed to improve maternal and child health. In a diverse country like India, there is a need to understand how the ASHA programme operates in different underserved Indian contexts, such as rural Manipur. METHODS: We undertook qualitative research to explore stakeholders’ perceptions and experiences of the ASHA scheme in strengthening maternal health and uncover the opportunities and challenges ASHAs face in realising their multiple roles in rural Manipur, India. Data was collected through in-depth interviews (n = 18) and focus group discussions (n = 3 FGDs, 18 participants). Participants included ASHAs, key stakeholders and community members. They were purposively sampled based on remoteness of villages and primary health centres to capture diverse and relevant constituencies, as we believed experiences of ASHAs can be shaped by remoteness. Data were analysed using the thematic framework approach. RESULTS: Findings suggested that ASHAs are mostly understood as link workers. ASHA’s ability to address the immediate needs of rural and marginalised communities meant that they were valued as service providers. The programme is perceived to be beneficial as it improves awareness and behaviour change towards maternal care. However, there are a number of challenges; the selection of ASHAs is influenced by power structures and poor community sensitisation of the ASHA programme presents a major risk to success and sustainability. The primary health centres which ASHAs link to are ill-equipped. Thus, ASHAs experience adverse consequences in their ability to inspire trust and credibility in the community. Small and irregular monetary incentives demotivate ASHAs. Finally, ASHAs had limited knowledge about their role as an ‘activist’ and how to realise this. CONCLUSIONS: ASHAs are valued for their contribution towards maternal health education and for their ability to provide basic biomedical care, but their role as social activists is much less visible as envisioned in the ASHA operational guideline. Access by ASHAs to fair monetary incentives commensurate with effort coupled with the poor functionality of the health system are critical elements limiting the role of ASHAs both within the health system and within communities in rural Manipur.